Effect of radiotherapy and chemotherapy on the survival rate of Asian Americans with nasopharyngeal carcinoma. Issue Volume 6:Issues 2(2022) (8th May 2022) - Chen, Allen M.; Qi, Lihong; Cress, Rosemary D.; Li, Yueju; Beckett, Laurel; Li, Baoqing
Abstract: Objective: To evaluate how the addition of concurrent chemotherapy to radiation therapy (RT) affects outcomes for Asian American patients with nasopharyngeal carcinoma. Methods: Using the California Cancer Registry – a population‐based, state‐sponsored database – Asian American patients with newly‐diagnosed, locally advanced nasopharyngeal carcinoma diagnosed between 1998 and 2010 were identified. The Kaplan–Meier method was used to analyze overall survival and cancer‐specific survival. Cox proportional hazards models were constructed to investigate the association with chemotherapy. Propensity score methods were used to control for measure confounders. Results: A total of 812 Asian Americans were included; 91 (11.2%) underwent RT alone, and 721 (88.8%) underwent RT with chemotherapy. The overall survival at 5 years was 65% with RT alone versus 72% with RT plus chemotherapy ( p = 0.31). The corresponding rates of cancer‐specific survival were 70% and 78% ( p = 0.35). Cox regression analysis confirmed a trend toward reduced mortality (HR 0.88, 95% CI 0.62–1.25, p = 0.37) in patients receiving RT and chemotherapy. Conclusion: Consistent with other studies that have been published, the addition of chemotherapy to RT was associated with improved clinical outcomes. Although this improvement did not reach statistical significance, the use of concurrent chemoradiation seems reasonable for Asian Americans with nasopharyngeal carcinoma. Abstract :